SUFFERING PHENOMENOLOGIE IN THE WORKS OF TARAS SHEVCHENKO: CHRISTIAN AND ANTROPOLOGICAL STUDIES - Bigun, O. A. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The analyses of suffering phenomena in the works of Taras Shevchenko is the subject of this article. The autobiographical experience and the creative embodiment of suffering phenomena are investigated on the view of Christian and antropological studies.